FENOMENA BULLYING DAN UPAYA PREVENTIF UNTUK MEMINIMALISIR EKSES PSIKOLOGIS PESERTA DIDIK - RIFIANI, DWI (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2023)
In many cases, generally the phenomenon of bullying leaves a psychological impact that is quite lasting and seems to be a nightmare for a person's life, especially for victims who do have social adjustments and are unable to adapt well. The negative impact experienced by someone who has been a victim of bullying is the main locus and becomes an accent and will be further elaborated by researchers. It is hoped that this effort will become a starting point for determining preventive steps that can be taken so that bullying in its various forms, even though it cannot be completely eliminated from the face of this earth, can at least be minimized so that the perpetrators of bullying think thousands of times about the negative impact if they do this. -, and students in general can determine the right steps if the action is indicated to happen to them. At least the policy holders are able to provide appropriate steps as a form of adult responsibility for the psychological and academic development of the future generation of the nation.Â Key word: Bullying Phenomenon, Â Preventive Efforts, Psychological Impact.